B Cell Homeostasis and Functional Properties Are Altered in an Hypochlorous Acid-Induced Murine Model of Systemic Sclerosis - Sanges, Sébastien; Jendoubi, Manel; Kavian, Niloufar; Hauspie, Carine; Speca, Silvia; Crave, Jean-Charles; Guerrier, Thomas; Lefèvre, Guillaume; Sobanski, Vincent; Savina, Ariel; Hachulla, Eric; Hatron, Pierre-Yves; et al. (Frontiers in Immunology, 2017)
Introduction. During systemic sclerosis (SSc), peripheral B cells display alterations in subset homeostasis and functional properties, and are a promising therapeutic target. However, there is only few data regarding whether these anomalies are accurately reproduced in animal models of SSc. Objective. In this work, we assessed the B cell homeostasis modifications in an experimental model of SSc (hypochlorous acid (HOCl)-induced mouse), both at a phenotypic and functional level, during the course of the disease. Methods. Balb/c mice underwent daily intradermal injections of HOCl (or PBS), and were then sacrificed at day 21 (early inflammatory stage) or day 42 (late fibrotic stage). For phenotypic studies, the distribution of the main spleen cell subsets (B cells, T CD4 and CD8 cells, NK cells macrophages) and splenic B cell subsets (immature, mature naïve, germinal center, antibody-secreting, memory, B1) was assessed by flow cytometry. For functional studies, splenic B cells were immediately MACS-sorted. Production of IL-6, CCL3, IL-10 and TGF-β was assessed ex vivo by RT-PCR and after 48h of culture by ELISA. Regulatory B cell (Breg) counts were quantified by flow cytometry. Results. Phenotypic analyses showed an early expansion of transitional B cells, followed by a late expansion of the mature naive subset and decrease in plasmablasts and memory B cells. These anomalies are similar to those encountered in SSc patients. Functional analyses revealed a B-cell overproduction of pro-inflammatory cytokines (IL-6 and CCL3) and an impairment of their anti-inflammatory capacities (decreased production of IL-10 and TGF-β, reduced levels of Bregs) at the early inflammatory stage; and an overproduction of profibrotic cytokines (TGF-β and IL-6) at the late fibrotic stage. These results approximate the anomalies observed in human SSc. Conclusion. This work reports the existence of anomalies in B cell homeostasis and functional properties in an animal model of SSc that approximate those displayed by SSc patients. These anomalies vary over the course of the disease, which pleads for their participation in inflammatory and fibrotic events. This makes the HOCl mouse a relevant experimental model for the study of B cells, and therefore B-cell targeted therapies, in SSc.